The Width of the Surgical Margin Does Not Influence Outcomes in Extremity and Truncal Soft Tissue Sarcoma Treated With Radiotherapy. (20th July 2016) - Ahmad, Rima; Jacobson, Alex; Hornicek, Francis; Haynes, Alex B.; Choy, Edwin; Cote, Gregory; Nielsen, G. Petur; Chen, Yen-Lin; DeLaney, Thomas F.; Mullen, John T.
Abstract : Background and Objectives: It is unclear whether the quantitative width of the surgical margin influences outcomes in patients with extremity and truncal soft tissue sarcoma (STS) treated with radiotherapy (RT). Methods: We performed a retrospective review of 382 patients with localized extremity or truncal STS who underwent limb-sparing surgery and RT from 1983 to 2010, and we analyzed the significance of resection margin status and quantitative margin width on outcomes. Results: Surgical margins were positive in 68 (18%) patients and negative in 314 (82%) patients. For those patients with a reported quantitative margin width ( n = 235), the width of the negative margin was ≤1 mm ( n = 128), >1 mm and ≤5 mm ( n = 79), and >5 mm ( n = 28). At a median follow-up of 82 months, the local recurrence rates were 5.4% and 11.8% for margin-negative and margin-positive patients, respectively. There were no differences in the rates of local or distant recurrence nor of any survival outcome based on the quantitative width of the surgical margin, provided that it was negative. Conclusions: In patients undergoing RT and limb-sparing surgery for STS, achieving a negative margin is essential for optimizing both local control and survival. However, the absolute quantitative width of the negative margin does not significantly influence outcome, and so attempts at wide margins of resection appear to be unnecessary. Importantly, the conclusions drawn from this study must not be applied to those patients undergoing surgery alone as the local treatment of their STS, in which case wider margins of resection may be necessary. Abstract : A retrospective review of 382 patients with localized extremity or truncal soft tissue sarcoma who underwent limb-sparing surgery and radiotherapy was performed. There were no differences in the rates of local or distant recurrence or of any survival outcome on the basis of the quantitative width of the surgical margin, provided that it was negative.